A Pilot Study of Transdisciplinary Graduate Capabilities, Interpersonal Communication, and Technical Competence : Bachelor of Applied Information Technology and Master of Social Work Student Partnership. - Gallagher, Hilary; Liang, Jianqiang; Torrisi-Steele, Geraldine; Ramsay, Sylvia (Journal of University Teaching & Learning Practice v.20 n.5 https://doi.org/10.53761/1.20.5.10, 2023)
Academics at Griffith university envisioned a complementary learning and supportive relationship could be developed between Bachelor of Information Technology (BAIT) students and Master of Social Work (MSW) students. Discussions between discipline specific staff highlighted that each discipline had strengths and expertise that could assist students to overcome challenges brought about by systemic changes in tertiary education, gaps in skillsets and curriculum, and workforce expectations. Pressures included students attending university from culturally and linguistically diverse backgrounds, the increasing importance of information technology (IT) in the classroom and workplace, as well as the requirement to communicate effectively across a range of disciplines. Working, interacting, and communicating effectively in cross-discipline and culturally diverse environments is a requisite for all graduates, however academics found there were few opportunities for students to partner across disciplinary silos. Staff from both disciplines collaborated to develop a conversational pedagogical framework to underpin a pilot program to support peer learning, using active problem-based learning with IT and social work students. The pilot program evidenced a complementary transdisciplinary, learning partnership and enabled students from IT to help students from social work develop IT skills, while social work students assisted IT students to become more confident in their interpersonal communication skills. [Author abstract]